Nectar secretion rhythms and nectar energetics of different Brassica spp. (Journal of Oilseed Brassica, 2026)
Studies on nectar secretion rhythms and nectar energetics of different Brassica spp. were conducted during 2019-20 at CCS Haryana Agricultural University, Hisar. Eleven genotypes of rapeseed-mustard belonging to different Brassica spp. i.e., B. juncea L. (RH 725, RH 0502, DRMRIJ-31, RCH-1), B. napus L. (HNS 0901), B. rapa L. var. Yellow Sarson (YSH-401), B. rapa L. var. Brown Sarson (BSH-1, B. rapa L. var. Toria (TH 68), B. carinata (HC-212), B. nigra Koch (NIGRA) and Eruca sativa (T27) were selected. The flowering phenology of various rapeseed-mustard genotypes/varieties showed that flowering initiation and cessation was earliest on TH 68 (32.7 and 81.7 DAS) while total flowering period was highest on RH 725 (53.0 DAS). The flower morphological parameters i.e. flower length, flower breadth, corolla and calyx length of different genotypes varied from 1.41 to 1.74 cm, 1.42 to 2.23 cm, 0.76 to 1.14 cm, 0.49 to 1.06 cm respectively and flower color was bright yellow in all genotypes/varieties. The mean amount of DNS (dry nectar sugar) per flower of various varieties/genotypes ranged between 0.63 to 1.50 mg at the time of peak flowering. The maximum mean amount of DNS was produced by the flowers of HC-212 and T-27 (1.50 and 1.49 mg/flower) followed by DRMRIJ-31, HNS0901, BSH-1, RCH-1, TH 68, YSH 401, RH0502, RH 725 (1.36, 1.23, 1.12, 1.03, 0.96, 0.93, 0.73, 0.73 mg/flowers). On other hand, highest amount of energy was produced by nectar of genotype HC-212 and T-27 (25.11 and 24.92 joules energy) followed by DRMRIJ-31, HNS 0901, BSH-1, RCH-1, TH 68, YSH 401, RH 0502, RH 725 (22.74, 20.54, 18.71, 17.30, 16.01, 15.50, 12.25, 11.81 joules energy) at the time of peak flowering. The Apis spp. were most abundant on variety TH 68 (16.77 bees/m2/10 min). The mean densities of A. mellifera was maximum (15.50 bees/m2/10 min) followed by A. cerana (12.90 bees/m2/10 min), A. dorsata (12.25 bees/m2/10 min) and A. florea (9.37 bees/m2/10 min).